(untitled) (KULT_online, 2017)
Futurologien: Ordnungen des Zukunftswissens by the editors Benjamin Bühler and Stefan Willer offers varied perspectives on knowledge of the future and knowledge in the future together with their potentials and problematic issues. The discussed volume is able to give examples of and inspiration for interdisciplinary research in the field of future knowledge from a cultural studies approach. It presents different orders of future knowledge in five sections and 36 articles. Its historical range covers examples and topics from antiquity to today. Many entries include disciplinarily diverse examples.